Hands-On Full Stack Web Development with Aurelia Develop Modern and Real-Time Web Applications with Aurelia and Node. js - Argüelles Rojas, Diego (Packt Publishing Ltd, 2018)
Isomorphic JavaScript has been a buzzword lately, allowing developers to utilize a single language throughout their web development stack and build cost-effective and scalable applications. This book is on one such modern web development stack which comprises of web technologies like MongoDB, Express.js, Aurelia.js, and Node